Effectiveness of an Ecosystem E-Booklet Containing Local Wisdom of Lake Rawa Pening to Improve Students’ Understanding of Environmental Care Concepts and Character - Al Ayyubi, Sholahudin Hasby Yusuf; Rusilowati, Ani; Saptono, Sigit; Irsadi, Andin (Unnes Science Education Journal, 2025)
Science learning aims to deepen students’ understanding of scientific concepts and equip them with the necessary scientific literacy skills for everyday life. How ever, the 2022 PISA survey results show that Indonesian students’ science literacy is still low. This study aims to assess the effectiveness of a science textbook based on the local potential of Grenden Village to improve the science literacy of junior high school students. The research method used is the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The research subjects were seventh-grade students at Junior High School 1 Puger. The research data consisted of effectiveness sheets, interviews, and documentation. The results showed that the developed textbook obtained effectiveness with an N-gain score of 0.58. The student response questionnaire obtained an average score of 82%. This study concludes that the developed textbook is valid, practical, and effective in improving the science literacy of junior high school students. The developed science textbook can be utilized to the fullest by students, teachers, and schools to effectively improve the science literacy of junior high school students, while further research can enhance the textbook by incorporating additional varied exercises and student activities tailored to their needs.